Specificity Protein 7 Is Required for Proliferation and Differentiation of Ameloblasts and Odontoblasts. (24th March 2018) - Bae, Ji‐Myung; Clarke, John C; Rashid, Harunur; Adhami, Mitra D; McCullough, Kayla; Scott, Jordan S; Chen, Haiyan; Sinha, Krishna M; de Crombrugghe, Benoit; Javed, Amjad
ABSTRACT: The Sp7/Osterix transcription factor is essential for bone development. Mutations of the Sp7 gene in humans are associated with craniofacial anomalies and osteogenesis imperfecta. However, the role of Sp7 in embryonic tooth development remains unknown. Here we identified the functional requirement of Sp7 for dentin synthesis and tooth development. Sp7 ‐null mice exhibit craniofacial dysmorphogenesis and are completely void of alveolar bone. Surprisingly, initial tooth morphogenesis progressed normally in Sp7 ‐null mice. Thus the formation of alveolar bone is not a prerequisite for tooth morphogenesis. Sp7 is required for mineralization of palatal tissue but is not essential for palatal fusion. The reduced proliferative capacity of Sp7 ‐deficient ectomesenchyme results in small and misshapen teeth with randomly arranged cuboidal preodontoblasts and preameloblasts. Sp7 promotes functional maturation and polarization of odontoblasts. Markers of mature odontoblast ( Col1a, Oc, Dspp, Dmp1 ) and ameloblast ( Enam, Amelx, Mmp20, Amtn, Klk4 ) are barely expressed in incisors and molar tissues of Sp7 ‐null mice. Consequently, dentin and enamel matrix are absent in the Sp7 ‐null littermates. Interestingly, the Sp7 expression is restricted to cells of the dental mesenchyme indicating the effect on oral epithelium–derived ameloblasts is cell‐nonautonomous. Abundant expression of Fgf3 and Fgf8 ligand was noted in the developing tooth of wild‐type mice. Both ligands were remarkably absent in the Sp7 ‐null incisor and molar, suggesting cross‐signaling between mesenchyme and epithelium is disrupted. Finally, promoter‐reporter assays revealed that Sp7 directly controls the expression of Fgf‐ligands. Together, our data demonstrate that Sp7 is obligatory for the differentiation of both ameloblasts and odontoblasts but not for the initial tooth morphogenesis. © 2018 American Society for Bone and Mineral Research.